Light Scattering by Noble Metallic Nanoparticles for Performance of Compound Solar Cells Enhancement - Nguyen, Lam Dinh (Communications in Physics, 2022)
Light scattering by noble metallic nanoparticles are of interest for a variety of applications due to the large electromagnetic field enhancement that occurs in the vicinity of the metal surface, and the dependence of the resonance photon energy on the nanoparticle size, shape, local dielectric environment, and material. Here, the influences of electromagnetic scattering by Au and Ag nanoparticles placed atop compound solar cells on optical absorption and photocurrent generation were investigated based on the variation in the noble nanoparticle densities. The results indicated that the short-circuit current and power conversion efficiency were strongly affected by the density and material of the noble nanoparticles. The great improvement of 28% in power conversion efficiency can be obtained with Au nanoparticle density of 2\(×\)108 cm-2. This improvement can be attributed to light scattering, light trapping, and surface roughness by noble nanoparticles. Furthermore, Au nanoparticles showed more efficient in solar cell power conversion efficiency improvement than Ag nanoparticles did although density of Au nanoparticle was lower than that of Ag nanoparticles.